Análise técnica, ambiental e econômica de um sistema fotovoltaico flutuante para o complexo Coremas-Mãe D’água (Paraíba) - Silva, Valéria Vieira da (2023)
Climate change and rising temperatures in some regions of the world have become a matter of global concern. The need to care for the environment and mitigate negative environmental impacts is extremely necessary and is being worked on in different parts of the world. Several countries are analyzing the best ways to implement technologies that can be useful for the generation of clean energy. This is the case of floating photovoltaic systems. Countries with the need to generate clean energy, but with little land space, began to analyze the feasibility of installing photovoltaic panels over water bodies, but with studies about this system, it was possible to perceive other features such as the reduction of evaporation that has been affecting several water bodies in a negative way, since even though it is a natural phenomenon, high temperatures have been intensifying its occurrence. For Brazil, some studies were initiated and the first floating photovoltaic plants were implemented, taking advantage of the country's hydroelectric plants. The city of Coremas is located in the Northeast of Brazil, more precisely in the intermediate region of Patos, and is known for its social, economic and environmental relevance as it contains the largest hydro complex in the state, Coremas - Mãe D’água. The general objective of this work was to analyze the technical, environmental and economic viability of a floating photovoltaic project for the Coremas - Mãe D'água hydro complex, so that this system can contribute to the generation of electricity, the reduction of the impact on the use of terrestrial spaces for the implementation of photovoltaic plants and the reduction of evaporation in the hydro complex. To enable a technical, economic and environmental analysis, the study was divided into chapters, where the first brings the presentation of the system, general considerations and the necessary points for the completion of the dissertation. In the second chapter, a bibliometric analysis and systematic review on the subject were carried out, managing to filter articles that could provide the basis for the necessary analyzes for the study design. In the third chapter, it was possible to design a floating photovoltaic system of 5 MW, so that it could cover a percentage of the complex, and thus perform the analysis of how much evaporation could be reduced using a floating photovoltaic system of the suspended type. For the fourth chapter, the financial viability of the system was analyzed considering distributed generation and financial indicators. With the results found, it was possible to perceive that the system has the possibility of being implemented, since it can bring environmental benefits, would be technically functional, and would bring renewable energy generation to the region with financial return.